2000
DOI: 10.1111/j.0014-3820.2000.tb00053.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Origins of Eusociality Among Sponge-Dwelling Shrimps (Synalpheus)

Abstract: Abstract. As the most extreme expression of apparent altruism in nature, eusociality has long posed a central paradox for behavioral and evolutionary ecology. Because eusociality has arisen rarely among animals, understanding the selective pressures important in early stages of its evolution remains elusive. Employing a historical approach to this problem, we used morphology and DNA sequences to reconstruct the phylogeny of 13 species of sponge-dwelling shrimps (Synalpheus) with colony organization ranging fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 107 publications
(49 citation statements)
references
References 67 publications
0
47
0
2
Order By: Relevance
“…Although eusociality has evolved repeatedly in Synalpheus (Duffy et al 2000;Morrison et al 2004;Didderen et al 2006), our phylogenetically controlled tests using new data for both development mode and social organization showed that eusociality was almost perfectly correlated with direct development, in which eggs hatch as crawling juveniles (figure 2). This association held regardless of whether the apparently variable species S. idios was coded as having swimming larvae (Maddison's CCT, p ¼ 0.005 -0.006 for the five trees) or crawling larvae (p ¼ 0.014 -0.016 for the five trees).…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…Although eusociality has evolved repeatedly in Synalpheus (Duffy et al 2000;Morrison et al 2004;Didderen et al 2006), our phylogenetically controlled tests using new data for both development mode and social organization showed that eusociality was almost perfectly correlated with direct development, in which eggs hatch as crawling juveniles (figure 2). This association held regardless of whether the apparently variable species S. idios was coded as having swimming larvae (Maddison's CCT, p ¼ 0.005 -0.006 for the five trees) or crawling larvae (p ¼ 0.014 -0.016 for the five trees).…”
Section: Resultsmentioning
confidence: 86%
“…The calculation, assumptions and rationale for using the E index for Synalpheus have been described previously (Duffy et al 2000). Briefly, the E index accounts for both reproductive skew and colony size, both of which vary considerably among Synalpheus species, and the index can be calculated from data collected over short time spans such as the point estimates available from our collections.…”
Section: (D) Quantifying Socialitymentioning
confidence: 99%
See 1 more Smart Citation
“…(d) Social structure Social structure was estimated using a variation of the eusociality index [38], calculated as E ¼ 1 2 (2 Â Q)/N, where N is colony size and Q is the number of reproductive females (sensu [22,23]). The eusociality index (E) incorporates both a colony's size and its reproductive skew making the simplifying assumption that all breeding individuals contribute equally to offspring production.…”
Section: (C) Reproductive Maturity and Sex Ratiosmentioning
confidence: 99%
“…The idea that co-operating groups can attend and defend resources more efficiently than individuals or less organised groups, and that eusociality may evolve by intense interactive competition for limited resources has existed for some time (Lin and Michener 1972;Alexander 1974;Evans 1977;Emlen 1991;Duffy et al 2000). The hypothesis was formalised by Witting (1997Witting ( , 2002b, who showed that if the level of interactive competition is sufficiently large, as is expected if the body mass is upward evolutionarily constrained relative to the energetic state of the organism (Section IV.2), then selection by density-dependent competitive interactions will select for large interacting units with the evolutionary optimum to the composition of individuals in the unit being a single female, a single male and a large number offspring workers that are sexually produced by the male and female (Witting 2002b).…”
Section: Eusocial Coloniesmentioning
confidence: 99%